Intermittent hypoxic training: A review/A pilot study - Hellemans, J. (1999)
1. IHT is an effective alternative to altitude training. 2. Side effects are minimal or absent. 3. IHT is often accompanied by a general improvement in health and well-being (confirming its use in the medical field). 4. There is likely to be an optimal dose for any individual athlete. This needs to be established. 5. Results compare favourably with other studies done on altitude training, in particular the live high-train low model. 6. Hypoxic training can be considered as additional training. There is potential for overload if the athlete does not adhere to the guidelines, especially in relation to recovery. 7. Some athletes will respond more than others, comparable with any form of training. 8. IHT is user friendly and easily accessible. It can be used by 4 athletes at any one time. 9. Current cost of a course of IHT is $385.00 per athlete, which is considerable cheaper than other forms of altitude training and simulation. 10. Of relevance are the significant health benefits obtained through IHT, which are unique for this particular method.